Al-Cr-Fe quasicrystals and their applications as reinforcements in the Ti based metal matrix composites - Li, Ruitao (2015)
In this study, the microstructural evolution and phase transformations of gas atomized Al-Cr-Fe powders during annealing process, spark plasma sintering (SPS) of Al-Cr-Fe powders and SPS of Ti/Al-Cr-Fe metal matrix composites (MMCs) were investigated. There are four phases identified in the annealed Al-Cr-Fe powders: icosahedral Al-Cr-Fe, decagonal Al-Cr-Fe, Al9(Cr,Fe)4 and Al8(Cr,Fe)5, with decagonal Al-Cr-Fe forming in the annealing process. Icosahedral Al-Cr-Fe is face-centered. Decagonal Al-Cr-Fe has a periodicity of about 1.2 nm along its periodic axis and it can be well superimposed by Penrose tilings. Al-Cr-Fe powders have been successfully sintered using SPS. With the rise of the sintering temperature from 650 ˚C to 800 ˚C, the relative density of the pellets increases from 70% to 99% and their microhardness increases from Hv 400 to Hv 810. The dominant densification mechanism of Al-Cr-Fe powders in the SPS process is powder rearrangement and dislocation motion. The SPS process promotes the formation of decagonal Al-Cr-Fe. Ti/Al-Cr-Fe MMCs with Ti as matrix and Al-Cr-Fe quasicrystals as reinforcements have been successfully prepared using high pressure SPS. Interfacial layer forms between Ti and Al-Cr-Fe during the sintering process. This layer mainly consists of Al3Ti and AlTi. With the increase of sintering pressure from 50 MPa to 300 MPa, the compositional changes of Al-Cr-Fe are reduced. The addition of Al-Cr-Fe particles to Ti matrix significantly improves the hardness and reduces the wear rate.